1999
DOI: 10.1046/j.1365-4362.1999.00846.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythroderma: a comparison between HIV positive and negative patients

Abstract: A large proportion of erythrodermic patients in this study were HIV positive. Inflammatory dermatoses were the commonest cause of erythroderma in all the patients studied. Drug reactions were the commonest cause in HIV positive patients. In the young black patient, erythroderma may be a marker for HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 25 publications
3
43
1
Order By: Relevance
“…29 cases of erythroderma were in the age group of 41-60 years while 10 cases were between 11-40 years, in above the age of 61 years-4 cases were noticed. It correlates the study of Akhyani M et al 2,5,3,4,6,7 The most common cause of these dermatitis in Spanish, Middle Eastern and Indian studies includes psoriasis and eczema . .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…29 cases of erythroderma were in the age group of 41-60 years while 10 cases were between 11-40 years, in above the age of 61 years-4 cases were noticed. It correlates the study of Akhyani M et al 2,5,3,4,6,7 The most common cause of these dermatitis in Spanish, Middle Eastern and Indian studies includes psoriasis and eczema . .…”
Section: Discussionsupporting
confidence: 76%
“…12,9,10 Drug reactions were the most common cause of erythroderma in HIV patients. 6 In the present study, the drug causing erythroderma was seen in five cases. Carbamazepine-induced reaction was seen in two cases.…”
Section: Discussionsupporting
confidence: 45%
“…To the best of our knowledge, there have been only 6 published cases in the English language literature of pathologically confirmed malignant syphilis in HIV-infected patients including ours (Table 1). We demonstrated the presence of spirochetes using immunohistochemical stain, while others used WarthinStarry stain (2,5,8) and Steiner stain (9,10).…”
Section: Discussionmentioning
confidence: 91%
“…Shulkin et al were able to identify only 14 cases of malignant syphilis in the English language literature since the early 1900's (2). However, more cases of the disease have been reported since the HIV epidemic, suggesting that HIV-infected patients may be at an increased risk (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). A multicenter retrospective study of 11,368 HIV-infected patients in Germany found that 151 (1.3%) patients were concurrently infected with syphilis, and 11 (7.3%) of those patients had lues maligna (16).…”
Section: Introductionmentioning
confidence: 99%
“…With advanced immunosuppression it becomes widespread and resistant to treatment and may predispose to erythroderma. 28,29 In African patients with short hair, thick and extensive yellowish scales of severe seborrhoeic dermatitis are more visible and can be very disfiguring.…”
Section: Inflammatory Skin Diseasesmentioning
confidence: 99%